ANALYSIS OF LEARNING EFFECTIVENESS IN THE 6+6 PROGRAM OF BATAM TOURISM POLYTECHNIC ON INTERNSHIP READINESS IN INDUSTRY - Lubis, Arina Luthfini; Supardi, Supardi; Wibowo, Andri; Santika, Kamelia (FORUM PAEDAGOGIK, 2025)
This study aims to analyze the effectiveness of theoretical and practical learning during the first six months of the 6+6 program at Batam Tourism Polytechnic on the readiness of Culinary Management Study Program students to undergo internships in the industry. The approach used is a mixed method, with a quantitative method in the form of a pre-test and post-test using multiple-choice questions analyzed using N-Gain, as well as a closed questionnaire. The qualitative method was carried out through an open questionnaire that was analyzed thematically. The results showed that all students experienced a significant increase in scores, with an average N-Gain of 0.72 (high category), which indicates effective learning in forming technical competencies. In addition, students and lecturers assessed that the curriculum, facilities, and integration of theory-practice had run well. However, there are still gaps in soft skills aspects such as professional communication, stress management, and mental readiness. Therefore, it is necessary to strengthen simulation-based learning and case studies so that graduates are not only technically ready, but also adaptive to industry challenges. This study contributes to the development of a vocational education curriculum based on work experience and becomes a reference for tourism education institutions in improving industrial internship programs.